Effect of Different Types of Fat on Lipid Metabolism in Rats - Mawahib B. Gasim Al-Farhaan; Azhar lateef Jabur; Hanaa S. Khadem; Mahdi M. Thuwaini (Institute of Medico-legal Publications Pvt Ltd, 2021)
The current study was conducted to inquiries and to determine the impact of different edible oils in experimental animals. Sixty albino rats that were randomly divided into 6 groups of 10 animals. The groups were fed on dietary without fat(control) (Group I), corn oil (Group II), butter fat (Group III), refined palm oil(Group IV) sunflower oil (Group V) and frying fat more than one for 8 weeks. After 12 h of diet removal, blood was collected to measure serum lipid profile (T.C., HDL, LDL and T.G.) levels. Rats of Group A were kept as control by feeding rat normal chow diet. Animals (rats) of groups B, C, D, E & F where fed by corn, butter, palm, sunflower and frying fat more than one oils respectively, at the dose of 15% in feed for 8 weeks. The procedures included determination of body weight gain, lipid profiles and histopathological lesions in different organs. All experimental rats declared advance or delay weight gain during the research period relying on type of oil. GC & GF oil treated group show highest significant (P<0.05) body weight gain, while GB, GD& gE show lowest significant (P<0.05, (P<0.05, P<0.03) Respectively than control group. Rats fed on diet include butterfat and frying more than one had the increment levels of TG, TC & LDL, and lower the HDL level than control group. On the other hand, corn, palm, sunflower oils led to the lower levels of TG, TC & LDL, but the same oils or viz (corn, palm, sunflower oils ) had incremented the HDL level as compare to control group.However, dietary intake of vegetable oils improved lipid profile, while butterfat and frying more than one had the contrary impact.